AYURVEDIC MANAGEMENT OF PRIMARY INFERTILITY DUE TO POLYCYSTIC OVARIAN SYNDROME ASSOCIATED WITH MULTIPLE UTERINE FIBROIDS: A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2018)
Infertility is a disease of the reproductive system defined by the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. As one of the leading causes of anovulatory infertility, it is believed that 5-10% of the reproductive-aged female population is living with polycystic ovary syndrome. Ayurveda considers the excellence of 4 factors- Ritu (ovulatory phase), Kshetra (garbhasaya), Ambu (proper nourishment to embryo), and Bija (healthy sperm and ovum) for a successful pregnancy. Impairment to any of these factors leads to Vandhytva or pregnancy failure. This case study helps to plan a treatment protocol for the patient with PCOS having infertility. A 25 yr old female having regular cycles came to OPD of Streeroga of IPGT & RA, having the complaints of weight gain and failure to conceive since 2 year of active married life. On presentation she was a medium sized woman with android body habits and had mild hirsute and acanthosis nigricans over nape of neck. Gynaecological examination revealed a normal sized uterus with no other abnormalities. Sonography revealed bulky ovaries with multiple small follicles with no evidence of ovulation along with small fibroids on anterior wall (1.8cmÃ—1.5cm) and posterior wall (2.7cmÃ—2.8cm). Her husbands semen analysis was normal. Based on clinical findings and investigation, anovulatory factor infertility due to PCOS was diagnosed along with fibroid. Virechana and Samana were decided due to both of these factors and Sthanyasodhana gana kashaya was selected as Samana drug. Treatment was done for 3 months, during treatment itself ovulation occured and the patient conceived after 3 months. This case being a Krichrasadhya vyadhi, proper care was taken including correction of the lifestyle and food habits. This case will help to understand the importance of Sodhana in gynecological disorders and explore the probable mode of action of Sthanyasodhana gana kashaya which helped in menstrual regulation.